Osteoporosis knowledge, health beliefs, and calcium intake among Malaysian chinese adults in Kampar, Perak - Thean, Hui Ru (2024)
Osteoporosis is a major health concern, characterized by low bone density and fragile bones. The Chinese population has the highest prevalence of hip fractures in Malaysia. Hence, the study investigated the relationship between osteoporosis knowledge, health beliefs, and calcium intake among Malaysian Chinese adults in Kampar, Perak. A cross-sectional study was conducted using convenience sampling among 205 Malaysian Chinese individuals aged 18–64 in Kampar. Participants completed a questionnaire that collected their sociodemographic data, osteoporosis knowledge, health beliefs, and calcium intake. The data were analysed using SPSS version 20, applying Chi-square and Spearman’s correlation tests. Firstly, the participants had a low osteoporosis knowledge level, with an average OPAAT score of 6.84 ± 2.92. In terms of health beliefs, Chinese adults in Kampar displayed low perceived susceptibility (14.87 ± 5.00), moderate perceived seriousness (17.81 ± 5.20), high perceived benefits (22.73 ± 3.75), moderate perceived barriers to calcium intake (15.61 ± 4.15), and high health motivation (21.26 ± 3.84). The average daily calcium intake was 530 ± 353.2 mg/day, with only 12.0% of participants meeting the recommended intake of 1000 mg/day or more. Significant associations were found between calcium intake and both osteoporosis knowledge (p = 0.045) and health motivation (p = 0.021). Furthermore, osteoporosis knowledge was significantly correlated with nearly all health belief categories. All health belief categories were correlated with each other, with the strongest correlation between perceived seriousness and health motivation (ρ = 0.304). Additionally, calcium intake was found to be correlated with age (ρ = 0.181), osteoporosis knowledge (ρ = 0.141), perceived benefits (ρ = 0.177), perceived barriers (ρ = -0.240), and health motivation (ρ = 0.176). These findings highlight the crucial need to prioritize raising awareness and strengthening health motivation in osteoporosis prevention programs targeted at the Malaysian Chinese population.